Fulfillment of Child Custody Rights After Divorce According to Law Number 35 of 2014 concerning Child Protection - Yovan Endik Irawanto; M Hidayat; Handyka Prayogi Lesmono (Faculty of Law, Merdeka University Surabaya, Indonesia, 2024)
Children are a trust and gift from the Almighty God, in whom the honor and dignity of being a complete human being is inherent, and every child who is born has his rights. The aim of this research is to fulfill custody rights for minor children after divorce, reviewing Law no. 35 of 2014 concerning fulfillment of child custody rights after divorce. The research method uses empirical methods through a qualitative approach. The results of research reviewing child custody after divorce in Indonesia in Law Number 35 of 2014 concerning child protection, its implementation has not been fully resolved properly, so it can be said that children's rights have not been fully protected. Neglect of children's rights to receive care from their own parents, neglect of Article 14 concerning children's rights to receive care, maintenance, education and living expenses. and Ignoring Article 26 concerning the obligations and responsibilities of parents in caring for, protecting and educating children.